MySRS - the development of web-based using PHP Laravel framework / Aisyah Hamizah Mahussin ... [et al.] - Mahussin, Aisyah Hamizah; Ab Rahman, Amri; Kairan, Omar; Ghazali, Jasrul Nizam; Abdul Malik, Mohd Azry; Mohd Yasin, Ahmad Bukhari (Unit Penerbitan, UiTM Kelantan, 2022)
Many organizations today, including in Malaysia, have implemented online management systems, as it is believed that technology and innthis sovation provide many benefits to those involved. The manual system lacks efficiency, too many manual forms and is time consuming, while the web-based system is more systematic, good management and prevents the loss of data. The goals of this project, MySRS - The Development of Web Based using PHP Laravel Framework, are to identify the data and information required within the organization, design the architecture and functionalities, and create an online management system to replace the manual system. The scope of this project is for the admin, who is the leader in Skim Rondaan Sukarela (SRS) to control the system and for public citizens to view MySRS to gain information, be promoted, and for registration. This system uses the Web Development Life Cycle for the methodology and the Waterfall Model because it is a suitable approach that can be used to develop web-based systems efficiently in a structured way. MySRS is developed using the PHP Laravel framework because it produces better website performance. According to the results of the user testing, it demonstrates positive feedback and excellent satisfaction from the leader of Skim Rondaan Sukarela (SRS) and the public. In conclusion, MySRS improves the management of the organization by reducing the manual workload. It helps people to do their jobs in an effective way and reduces data handling.